Synthesis and luminescent properties of SrTiO₃:Pr³⁺ phosphors prepared by sol-gel method - Marchylo, O.M.; Zavjalova, L.V.; Nakanishi, Y.; Kominami, H.; Hara, K.; Belyaev, A.E.; Svechnikov, G.S.; Fenenko, L.I.; Poludin, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
New red SrTiO₃:Pr³⁺ phosphor for the field emission displays application was prepared using the sol-gel method. The reaction between starting materials SrCl₂, Ti-(Oi-C₃H₇)₄ and PrCl₃ resulted in a mix of compounds transformed to single-phase SrTiO₃:Pr after its annealing in air. Optimal technological conditions for preparation of efficiently radiating SrTiO₃:Pr³⁺ phosphors were found. Both photoluminescence and cathodoluminescence spectra showed the high intensity red peaks at the wavelength λmax = 617 nm. The high luminance of 300 cd/m² was obtained at the anode voltage of 10 kV.